Milk Quality, Curd, and Whey Percentages of Holstein Friesian Cows at Different Lactation Phases - Syawal, S.; Utamy, R.F.; Ako, A.; Hasbi , H.; Rahman, A. A.; Ramadan, Z.; Mufliha, R. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
The lactation phase of dairy cows is very important in determining the quality of milk produced. The lactation phase is divided into three phases: early, mid, and late lactation. The objective of this study was to determine the milk quality and percentage of curd and whey of Holstein Friesian dairy cows at different lactation phases. This study was conducted using a completely randomized design (CRD) with 3 treatments and 5 replicates of each treatment. The treatments in this study were P1 = early lactation, P2 = middle lactation, and P3 = late lactation. The research data were processed through the SPSS application using the ANOVA test, and if there was a difference between treatments, it would be further tested using the Duncan test. The lactation phase significantly affected (P < 0.05) the fat content and curd production of Holstein Friesian cow milk, but did not significantly affect the protein content, pH, specific gravity (SG), and viscosity of Holstein Friesian cow milk. The lactation phase has a significant impact on the milk quality and percentage of curd and whey in Holstein Friesian dairy cows. It has been observed that during the late lactation phase, the milk quality tends to be higher, which is a noteworthy finding for dairy farmers. Keywords: Phase of lactation, physical quality, chemical quality, curd, and whey